Design e tecnologia: estudo sobre tecnologias da informação aplicadas a objetos - Lins, Leonardo Antonio (2017)
This work investigates information technologies applied to objects and seeks to comprehend how computer distribution in domestic environments can affect an interacting individual attention to objects that offer computational capabilities earlier applied only to computers. The research is set off from the presentation of a technological panorama where the possibility of pulverization of small computers integrated in domestic objects is enabled by the application of the concept of Internet of Things through the possibility of a wireless connection and the use of sensors and actuators. Based on the contribution of authors such as Marc Weiser, Amber Case and Claire Rowland, the concepts of computing dispersed through a domestic environment are analysed. Later on, the study fundamentals where attention is explored are presented, as well as the impact of technological changes expressed during industrialization, period when the attention issue is manifested in Jonathan Crary’s text. After discussions on attention matters, Weiser’s formulation regarding rudiments of a Calm Technology that is capable of offering interactions without demanding the constant of the individual’s attention is presented. Finally, with the intent of raising from interaction design and interface fundamentals, elements that constitute the approach of user’s experience are studied, in order to facilitate the presentation and discussion of examples of connected and interactive objects from an interaction between individuals and connected objects perspective. The application of concepts from interaction design with distributed technology is contemporary and still experimental, enabled by technological development, however, the discussion of these applications exposes the need for comprehension that objects become interactive, as well as computers and mobile devices